How do post-disaster policies influence household-level recovery? A case study of the 2010-11 Canterbury earthquake sequence, New Zealand. (15th June 2021) - He, Lulu; Dominey-Howes, Dale; Aitchison, Jonathan C.; Lau, Annie; Conradson, David
Abstract: This study analyses the success and limitations of the recovery process following the 2010–11 earthquake sequence in Christchurch, New Zealand. Data were obtained from in-depth interviews with 32 relocated households in Christchurch, and from a review of recovery policies implemented by the government. A top-down approach to disaster recovery was evident, with the creation of multiple government agencies and processes that made grassroots input into decision-making difficult. Although insurance proceeds enabled the repair and rebuilding of many dwellings, the complexity and adversarial nature of the claim procedures also impaired recovery. Householders' perceptions of recovery reflected key aspects of their post-earthquake experiences (e.g. the housing offer they received, and the negotiations involved), and the outcomes of their relocation (including the value of the new home, their subjective well-being, and lifestyle after relocation). Protracted insurance negotiations, unfair offers and hardships in post-earthquake life were major challenges to recovery. Less-than-favourable recovery experiences also transformed patterns of trust in local communities, as relocated householders came to doubt both the government and private insurance companies' ability to successfully manage a disaster. At the same time, many relocated households expressed trust in their neighbours and communities. This study illuminates how government policies influence disaster recovery while also suggesting a need to reconsider centralised, top-down approaches to managing recovery. Highlights: Government policies influence recovery by affecting post-disaster experiences. Centralised governance approach weakens community resilience. Complex claim-resolving procedures undermine recovery. Top-down governance transforms the pattern of trust in local communities.